Scattering of Long Waves by Freely Oscillating Submerged Plates - Chen, Yongbo; Hayatdavoodi, Masoud; Zhao, Binbin; Ertekin, R. Cengiz (Journal of Offshore Mechanics and Arctic Engineering, 2024)
We consider a horizontal, submerged plate in shallow water that is allowed to oscillate in the vertical direction due to the wave loads. The plate is attached to a linear spring and damper to control the oscillations. The focus of the study is on the transformation of the wave field by the submerged oscillating plate. To estimate energy scattering, wave reflection and transmission coefficients are determined from four wave gauges; two placed upwave and two placed downwave of the oscillating plate. The flow is governed by the nonlinear Level I Green-Naghdi (GN) equations, coupled with the equations of the vertical oscillations of the plate. Time series of water surface elevation recorded at gauges upwave and downwave of the plate obtained by the GN model are compared with the available laboratory experiments and other data, and very good agreement is observed. Wave reflection and transmission coefficients are then determined for a range of involved parameters, including wave conditions (wavelength and wave height), initial submergence depth of the plate, plate length, and the spring-damper system attached to the plate. It is found that a submerged oscillating plate can have a remarkable effect on the wave field, and that nonlinearity plays an important role in this wave-structure interaction problem. Discussion is provided on how the wave reflection and transmission coefficients vary with the wave conditions, plate characteristics, initial submergence depth and spring-damper system properties